Investigation of intake closing timing on the flow field and combustion process in a small-scaled Wankel rotary engine under various engine speeds designed for the UAV application. (15th June 2023) - Yang, Jinxin; Wang, Huaiyu; Ji, Changwei; Chang, Ke; Wang, Shuofeng
Abstract: This paper aims to reveal the effect of intake closing timing, and engine speed on the flow field, flame propagation, combustion characteristics, and emissions formations of a small-scaled side ported hydrogen-fueled Wankel rotary engine. For this reason, a three-dimensional dynamic simulation model was established using a reasonable turbulent model coupled with a kinetic reaction mechanism and validated by the experimental data. Simulation results show that an earlier intake closing timing increases the volumetric efficiency and increases intake loss. The increasing speed improves the volumetric efficiency while causing a higher intake loss. There are two peaks of the turbulence kinetic energy during the intake stroke. The first one is caused by the airflow hitting the wall, and the other is due to the backflow. During the flame development period, due to the strong unidirectional flow in the combustion chamber, which is not conducive to flame propagation backward. This phenomenon is more pronounced at higher engine speeds, resulting in a merged flame front not exceeding the trailing spark plug. The lean combustion leads to a lower in-cylinder combustion temperature, deteriorating the NOx generation environment. This paper provides a feasible method for matching the operating conditions and intake system. Highlights: The shape and area of the intake port varies with the intake closing timing. Dual-spark plug flame propagation pattern is proposed. The leakage of gas to adjacent cylinder is reduced at 8000 rpm.